Model of the Empowerment of Change Management Governance Based in the Higher Education Quality - Sanusi, Anuar; Y.Irianto, Suhendro; Fauzi, Fauzi (Opción, 2019)
The change management in higher education governance is able to adapt into a global change of businesses and sustainable technologies. This study aims to assess the empowerment profile-based on the change management governance quality. This research uses quantitative method to collecting data and documentation by triangulation technique to determine the main factors of quality policy, mechanism of reference preparation theory to fit theoretical reference and quality guarantee. The results show that there are changes of quality based on the governance management because of the main factor or the quality target indicators. The next result is the leader- ship variable which is main factor in accountable management, which of the good indicators to assess the overall management of universities proven indirectly to have is one a positive impact on changes in the performance of higher education management. This shows evidence that universities must consider the implementation of visionary leadership factors to improve the performance of university management.